Wewenang Otorita Ibu Kota Nusantara Selaku Pemegang Hak Pengelolaan Kawasan Ibu Kota Nusantara - Fauzi, Fahrul; Sujadi, Suparjo (Tunas Agraria, 2023)
The relocation of the National Capital is a national strategic project to create a sustainable city that attracts investment from both within the country and abroad. The Nusantara Capital Authority, which is responsible for the preparation, development, and management of the city, has authority over the management of land included in the assets controlled by the authority. This study aims to identify the extent of the authority of the rights of management holders in Nusantara Capital and its implications on investment activities there. The research employs a doctrinal research method, utilizing a normative juridical approach through the analysis of legislative policies in relation to their actual implementation. The study reveals that the Nusantara Capital Authority holds the power to formulate land allocation plans in accordance with the master plan of the Nusantara Capital, to utilize land management rights, and/or to collaborate with other parties. Additionally, the authority has the prerogative to determine rates and/or annual dues payable by land rights holders above the management rights of the Nusantara Capital Authority. The authority vested in the Nusantara Capital Authority as the holder of the rights of management can synergistically align with the strategy of attracting investors to invest in Nusantara Capital, particularly concerning the regulation of the duration of land rights with third parties in the Land Utilization Agreement.   Pemindahan Ibu Kota Negara adalah proyek strategis nasional untuk menciptakan kota berkelanjutan yang menarik investasi baik dari dalam negeri maupun luar negeri. Otorita Ibu Kota Nusantara, yang bertugas untuk persiapan, pembangunan, dan pengelolaan kota tersebut, memiliki wewenang atas pengelolaan tanah yang termasuk dalam aset yang dikuasai oleh otorita. Penelitian ini bermaksud untuk mengidentifikasi sejauh mana kewenangan pemegang hak pengelolaan di Ibu Kota Nusantara dan implikasinya pada aktivitas investasi di sana. Penelitian ini menggunakan metode penelitian doktrinal atau pendekatan yuridis normatif dengan cara analisis kebijakan perundang-undangan terhadap realitas implementasi yang terjadi. Penelitian ini mengungkap bahwa Otorita Ibu Kota Nusantara memiliki wewenang untuk menyusun rencana peruntukan tanah sesuai rencana induk Ibu Kota Nusantara, menggunakan tanah hak pengelolaan dan/atau mengkerjasamakan dengan pihak lain, dan menentukan tarif dan/atau uang wajib tahunan yang harus dibayar mitra pemegang hak atas tanah di atas hak pengelolaan Otorita Ibu Kota Nusantara. Wewenang Otorita Ibu Kota Nusantara selaku pemegang hak pengelolaan dapat berjalan beriringan dengan strategi menarik penanam modal untuk berinvestasi di Ibu Kota Nusantara, khususnya kewenangan untuk mengatur jangka waktu hak atas tanah dengan pihak ketiga dalam Perjanjian Pemanfaatan Tanah.